Formulating Relations: An Approach to the smyt-Formula - Olabarria, Leire (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
The language of monumental inscriptions on Middle Kingdom stelae is often regarded as highly standardised and formulaic, thus its potential for assessing social practices is considered to be fairly limited. An analysis that integrates textual and contextual evidence may, however, facilitate a better understanding of some formulae and the role those stelae played in the construction of contemporary social models. The rare smyt -formula is attested in nine objects of the late 12th or early 13th dynasty. Most of these are stelae found at Abydos, hence saturated with the site’s cultic importance. Although their disparate stylistic features rule out their being products of a single workshop, the use of the formula and its arrangement after a list of personal names is strikingly consistent. The way in which people, who are mentioned on those lists, are related to the dedicatees of the monuments may provide a clue as to why this formula emerged in the late Middle Kingdom, a time when kinship relations were often celebrated and commemorated on stelae in the context of the ritual landscape of Abydos. Moreover, the smyt -formula signposts a latent tension between two modes of group formation, focused respectively on ego or on his ancestors.